2022
DOI: 10.1038/s41467-022-34830-4
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-induced LRP3 downregulation promotes cartilage degeneration in osteoarthritis by targeting Syndecan-4

Abstract: Emerging evidence suggests that osteoarthritis is associated with high cholesterol levels in some osteoarthritis patients. However, the specific mechanism under this metabolic osteoarthritis phenotype remains unclear. We find that cholesterol metabolism-related gene, LRP3 (low-density lipoprotein receptor-related protein 3) is significantly reduced in high-cholesterol diet mouse’s cartilage. By using Lrp3−/− mice in vivo and LRP3 lentiviral-transduced chondrocytes in vitro, we identify that LRP3 positively reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Lipid and cholesterol accu-mulation are proposed as the contributing risk factors for OA development. [46] Similar to our findings, SIRT3 exerts protective actions on articular cartilage in aging-related OA model. [12] Our gain-of-function experiments further suggested that activation of SIRT3 recouples the mitochondrial redox balance, a notable feature in OA, [47] to attenuate chondrocytes injury.…”
Section: Discussionsupporting
confidence: 89%
“…Lipid and cholesterol accu-mulation are proposed as the contributing risk factors for OA development. [46] Similar to our findings, SIRT3 exerts protective actions on articular cartilage in aging-related OA model. [12] Our gain-of-function experiments further suggested that activation of SIRT3 recouples the mitochondrial redox balance, a notable feature in OA, [47] to attenuate chondrocytes injury.…”
Section: Discussionsupporting
confidence: 89%
“…MVK is involved in regulation of cholesterol and isoprene biosynthesis, 35 and the identified variant in MVK was positively associated with cholesterol levels in publicly available datasets. The fact that the variant is suggestively protective (OR = 0.79) while being positively associated with cholesterol levels may seem counterintuitive given the plausible negative relationship between cholesterol and osteoarthritis 36,37 . However, since none of the identified variants reached genome‐wide significance or have been examined for causality, further speculation about the pathophysiological relevance of the variants and their related genes is currently unwarranted.…”
Section: Discussionmentioning
confidence: 99%
“…Low-density lipoprotein (LDL) receptor-related proteins (LRPs) play an important part in the regulation of cholesterol metabolism and have recently been shown to be involved in the onset and progression of OA ( 88 ). Cao et al investigated the potential role of LRP3 in OA pathogenesis and therapy ( 85 ). In TNF-α stimulated rat OA chondrocytes, lentiviral-mediated overexpression of Lrp3 induced the expression of the anabolic genes COL2A1, ACAN, and SOX9, and restored expression of proteoglycan and GAG.…”
Section: Discussionmentioning
confidence: 99%